Transformational Leadership, Team Cooperation, and Motivation in Shaping Patient Safety Culture Among Healthcare Professionals - Suci Romadhona; Kemala Rita Wahidi; Johanes; Titi Sundari; Farida Murtiani; Rokiah Kusumapraja (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Patient safety remains a critical global health agenda, as emphasized by the WHO and IOM. Fostering a robust patient safety culture within hospitals is paramount for minimizing adverse events and improving the quality of care. Understanding the psychosocial factors that drive this culture is essential for effective organizational interventions. This study aims to explore the direct and indirect effects of transformational leadership and team cooperation on patient safety culture, with a particular focus on assessing the mediating function of motivation within these relationships among healthcare professionals. Methods: An analytical cross-sectional research design was applied in this study. Study utilized a survey to collect data from 198 Healthcare Providers (HCPs) at Sulianti Saroso Infectious Disease (SSIDH). The primary instrument was the Hospital Survey on Patient Safety Culture (HSOPS) Version 2.0. Data analysis involved Structural Equation Modelling (SEM) based on Partial Least Squares (PLS-SEM) using SmartPLS 4.0 to test the proposed causal relationships. Results: Descriptive analysis showed that the variables of Transformational Leadership, Team Cooperation, Motivation, and Patient Safety Culture were all in the moderate category. However, hypothesis testing revealed significant findings. Both transformational leadership and team cooperation demonstrated a direct and significant positive influence on patient safety culture. Crucially, motivation was found to significantly mediate the relationship between transformational leadership and safety culture, as well as the relationship between team cooperation and safety culture. Conclusion: This study confirms that transformational leadership and teamwork are crucial factors that effectively enhance patient safety culture. The central finding of this study is the vital role of motivation as a psychological mechanism that translates managerial initiatives and team collaboration into proactive safety behaviors. Therefore, the practical recommendations from this research focus on strategies that directly target motivation, such as strengthening programs for recognition and responsibility, accompanied by improved interprofessional communication and more specific leadership training programs.